2017
DOI: 10.1097/pcc.0000000000000945
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of the Pediatric Acute Lung Injury Consensus Conference Definition of Acute Respiratory Distress Syndrome*

Abstract: Applying the Pediatric Acute Lung Injury Consensus Conference definition of acute respiratory distress syndrome has the potential to significantly increase the number of acute respiratory distress syndrome patients identified, with a lower overall mortality rate. However, severe acute respiratory distress syndrome is associated with extremely high mortality, particularly if present at 24 hours after initial diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 13 publications
8
73
3
3
Order By: Relevance
“…The introduction of OSI allows the application of a standardized definition to children without an arterial line [13]. According to a recent study, applying the PALICC definition more paediatric patients with ARDS may be identified and the mortality rate may be lowered except for the more severe group [14]. Epidemiological data and animal studies suggest there are age-dependent differences in distribution, causes and peculiarity of ARDS, whereas the pathophysiology of ARDS does not change.…”
Section: Berlin Definition Of Ards Validated For Adults: But What Abomentioning
confidence: 99%
“…The introduction of OSI allows the application of a standardized definition to children without an arterial line [13]. According to a recent study, applying the PALICC definition more paediatric patients with ARDS may be identified and the mortality rate may be lowered except for the more severe group [14]. Epidemiological data and animal studies suggest there are age-dependent differences in distribution, causes and peculiarity of ARDS, whereas the pathophysiology of ARDS does not change.…”
Section: Berlin Definition Of Ards Validated For Adults: But What Abomentioning
confidence: 99%
“…One major strength is that we prospectively screened and identified patients with PARDS using the PALICC definition . Strikingly, the adult definitions only identify a subset of children with PARDS per the PALICC criteria . Thus, our findings highlight the outcomes of the “new” cohort of PARDS survivors and provide an anchor for future studies in this field.…”
Section: Discussionmentioning
confidence: 77%
“…Compared to the adult Berlin 3 and American European Consensus Conference 12 definitions, the PALICC definition identifies nearly twice as many children with ARDS, including many with milder disease but also a subset of patients with severe ARDS that were not identified by adult definitions. 13,14 Overall mortality was lower when using the PALICC definition, 13 suggesting that the characteristics of the "new" cohort of PARDS survivors and their outcomes may differ from those of children identified through the adult definitions.…”
Section: Introductionmentioning
confidence: 99%
“…We combined four previously published datasets of invasively mechanically ventilated children with PARDS (15)(16)(17)(18). Two of the datasets were gathered retrospectively by reviewing the electronic health records of pediatric ICU (PICU) patients admitted to Children's Hospital Los Angeles (CHLA) from 2000 to 2007 (15) and 2009 to 2013 (16). One dataset was gathered prospectively from patients admitted to the Children's Hospital of Philadelphia (CHOP) from 2011 to 2016 (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…In general, there is reluctance to escalate PEEP above 10 cm H 2 O, particularly for younger children (8,11). Through secondary analysis of aggregated data from four previously published studies of children with pediatric ARDS (PARDS) (11,(15)(16)(17)(18), we sought to determine if patients managed with PEEP levels lower than recommended by the ARDSNet table for a given FI O 2 in actual practice had higher mortality than patients who were managed with PEEP levels consistent with or higher than recommended by the ARDSNet table.…”
mentioning
confidence: 99%